Peningkatan Hasil Belajar Tema Pengalamanku Muatan Pelajaran Bahasa Indonesia melalui Model Benar Salah Berantai Berbantuan Kartu Kata pada Siswa Kelas II SD Negeri 2 Kedungsari - Ismanita Sapuji (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
The learning outcomes of class II students at SDN 2 Kedungsari, Singorojo District, Kendal Regency in semester 2 of the 2021/2022 Academic Year on the theme My experience, the content of Indonesian lessons is low. This happens because learning is dominated by the teacher, only a small proportion of students can follow the lesson well. To minimize teacher dominance in learning, teachers need to plan and develop learning models and media. One of the learning models that can be used is the true-false model with the help of word cards. This study uses Classroom Action Research (CAR), which consists of 3 cycles with 2 meetings in each cycle. The subjects in this study were grade II students at SD Negeri 2 Kedungsari, Singgorojo District, Kendal Regency, semester 2 of the 2021/2022 academic year, with a total of 20 students consisting of 9 male students and 11 female students. The results showed that the average value of students in the initial conditions was 63.50 with a completeness percentage of 45%. This condition experienced an increase in the average value of students in cycle I, which was equal to 70.00 and the percentage of completeness was 60.00%. In cycle II the average value of students is equal to 75.00 and the percentage of completeness is 75%. Then after continuing to cycle III the average value of students again increased by 80.00 with a completeness percentage of 90%. Thus it can be concluded that the application of the true-false learning model with the help of word cards can improve learning outcomes with the theme My experience, Indonesian language lesson content for second grade students at SD Negeri 2 Kedungsari, Singorojo District, Kendal Regency, semester 2 of the 2021/2022 academic year.